Rewriting the North: Place, Nation, and the Cultural Politics of Devolution - Ashbridge, Chloe (2021)
Between the 1997 devolutionary moment and the 2016 Brexit-vote, the Union’s continuity has become increasingly uncertain. In England, the fraught relationship between the North and the South East of England has been at the centre of debates regarding devolution, with the ‘English Question’ taking on an explicitly regional dimension. At the same time, British devolution developed a distinctively cultural registration, functioning on the one hand as a surrogate for national parliamentary representation; and, on the other, regional decentralisation, an attempt to disrupt the status of London as Britain’s cultural epicentre. Rewriting the North extends this debate by appraising the relationship between British constitutional culture and the literary North. To do so, this thesis advances two interlinked arguments. First, that Northern England has functioned in the national imagination less as a geographical territory than as a culturally loaded spatial metaphor for a nexus of socio-economic and constitutional tensions throughout Britain. Second, that this construction of the North has been augmented by a persistent cultural North-South divide, which has served as a bulwark of the Union in securing the continued suppression of a national England.